Mutually conditional development of small business and social sphere mechanism - Tetyana Karpova (Cхід)
The article suggests the conception of mutually conditional development of small business and social sphere mechanism, based on the synthesis of effective forms, instruments and methods of its realization. It stipulates for state and non-state support of small business, systems of their provision, and helps to activate the development of small business and increase the level of economic and social welfare of workers and all society. The main goal of the author's conception is to increase the role and importance of small business in development of national economy's social sphere, the strengthening of its competitiveness on domestic and international markets and its influence on the economic and social processes in society. The process of mutually conditional development of small business and social sphere, as a structural unit, is an object of state policy management of the small enterprise and social sphere development at national and regional levels. The mechanism of mutually conditional development of small business and social sphere is based on the normative-legal, organizational, resource, informative, financial and credit systems of their provision. The realization of offered mechanism will allow to stimulate the activity of enterprises, flexible management of small business in relation to an external environment. This will provide them sufficient efficiency and competitiveness on domestic and international markets, and will strengthen their influence on economic and social processes in society.